Science and Practice of Pressure Ulcer Management (Springer London, 2018)
This updated volume provides the current knowledge on the diagnosis, treatment, management, and prevention of pressure ulcers. Chapters on the early detection of pressure ulcers, negative pressure therapy, pressure ulcers in pediatric patients, adjunctive therapies, surgical management of pressure ulcers, and innovation in pressure ulcer research and practice are included. This second edition aims to be the primary reference for pressure ulcers from diagnosis and prevention to management and treatment options. The book is relevant to dermatology clinicians, vascular surgeons, and dermatology nurses.